Students' Perceptions on the Use of E-Portfolio for Learning Assessment: A Case Study - Chalim Fathul Muin; Hafidah Hafidah (ELITE Association Indonesia, 2021)
E-portfolio is implemented in Indonesian universities to build learners’ capacity in monitoring and managing the learning in a technology-enhanced environment. In this regard, it is substantial for the institutions to acknowledge the learners' perspective in using the e-portfolio for the purpose of continuous development. This study was aimed at probing students' perceptions of utilizing e-portfolio for learning at the university. The study was qualitatively conducted as a case study. The subjects were 16 undergraduate students of the seventh semester in a university. The data were obtained by conducting interviews and disseminating a questionnaire. The results of the study revealed that most participants demonstrated positive views towards the use of e-portfolio. Further, the participants acknowledged some crucial benefits of utilizing the e-portfolio. They were extended to; increasing the motivational beliefs and self-efficacy, learning new things, accomplishing the English tasks effectively, giving beneficial effects for the learning, and improving students' ability in English. The findings are expected to bring light to stakeholders to consider the use of e-portfolio to encourage students' learning enthusiasm and engagement.